Cloud Computing and Security Issues (International Journal of Engineering and Computer Science, 2017)
The cloud computing model for delivering computing services offers cheap access to a variety of standardized services from various providers. But after outsourcing a service to the cloud, the owner no longer controls the platform on which the service runs. The user is bound to trust the cloud provider for correctness, privacy, and integrity of its data and computations. Cryptographic mechanisms can reduce such trust by allowing the user to protect its data and computations, as well as to verify aspects of remote computation. Benefits of cloud storage are easy access, it means access to your knowledge anyplace, anyhow, anytime, scalability, resilience, cost efficiency, and high reliability of the data. Each and every organization is moving its data to the cloud, means it uses the storage service provided by the cloud provider. So there is a need to protect that data against unauthorized access, modification or denial of services etc. To secure the Cloud means secure the calculations and storage databases hosted by the Cloud provider. This paper describes  different security issues to the cloud , different cryptographic algorithms adoptable to better security for the cloud.